The Affective Becoming of Matter. Notes on the Emergence of New Materialisms - Pellicer Planells, Milagros (Las Torres de Lucca. International Journal of Political Philosophy, 2026)
The present article addresses the emergence of New Materialisms as a plural and transdisciplinary framework in response to the limitations that schools of thought articulated within the Linguistic Turn posed when dealing with the relationship between matter and culture. Drawing upon the debate by Sara Ahmed and Noela Davis, initiated in this context, this study delves into the intricate intertwinement of the New Materialisms and Contemporary Feminism, emphasising the inextricably feminist nature of neo-materialist thought, whose novelty does not lie in a rupture with prior traditions but in their potentialisation. To this end, the figure of Baruch Spinoza will be explored through the theoretical frameworks of Gilles Deleuze, Rosi Braidotti and Elizabeth Grosz, amongst other authors, with the aim of conceptualising a relational ontology that transcends dualist methodologies via the renaturalisation and decentrement of the human subject. This will engender a feminist, impersonal and imperceptible political transformation that regards all bodies —human and non-human— in terms of an affective, agentive and vibrant matter.
Keywords: New Materialisms; Matter; Culture; Feminism; Affects